Interface modified electron transport layer, perovskite solar cell and preparation method thereof
By modifying the SnO2 electron transport layer with ADA-type large π conjugated material GCC, the problems of energy level mismatch and defects between SnO2 and perovskite were solved, thereby improving the photoelectric conversion efficiency and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202210282788.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-22
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-03-22
AI Technical Summary
SnO2, as an electron transport layer material, suffers from conduction band energy level mismatch with perovskite and charge recombination problems caused by intrinsic defects in perovskite solar cells, affecting device efficiency and stability.
The SnO2 electron transport layer was modified at the interface using ADA-type large π conjugated material GCC to regulate its work function and passivate defects, forming a dipole to improve matching performance.
It effectively reduces the work function of SnO2, passivates oxygen vacancy defects, improves electron mobility, enhances carrier separation and transport efficiency, and improves photoelectric conversion efficiency and device stability.
Smart Images

Figure CN116847666B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of green and sustainable energy, specifically relating to an electron transport layer based on an ADA-type large π conjugated material interface modification, a perovskite solar cell and its preparation method. The use of this material can significantly improve the photoelectric conversion efficiency and stability of the battery device. Background Technology
[0002] Since its initial report in 2009, perovskite solar cells (PSCs) have seen a rapid increase in photoelectric conversion efficiency, currently reaching a certified efficiency of 25.7%. This efficiency is comparable to commercially available silicon-based solar cells, making them a promising next-generation solar cell. In addition to their high photoelectric conversion efficiency, PSCs also possess advantages such as simple fabrication processes, low manufacturing costs, and the ability to be fabricated into flexible devices, thus attracting widespread attention from the research and industrial communities.
[0003] Electron transport layer materials with excellent interfacial charge separation and transport capabilities are crucial for achieving high-performance photoelectric cells (PSCs). PSCs originated from dye-sensitized solar cells, so TiO2 has been widely used as the electron transport layer in many research studies. However, TiO2-based devices exhibit significant hysteresis, which inevitably reduces photoelectric performance and long-term stability. Recent research suggests that SnO2 is a promising alternative to TiO2 as the optimal electron transport layer material. This is primarily due to SnO2's superior visible light transmittance, higher electron mobility, low-temperature processing capability, insensitivity to ultraviolet light, and good chemical stability compared to TiO2. However, SnO2, as an electron transport layer, has poor conduction band energy level matching with perovskite (Li et al. Adv. Funct. Mater. 2020, 2004 209); in addition, the intrinsic defects of SnO2 can trap electrons, which can easily cause severe charge recombination when applied to PSC, thereby reducing device efficiency (Sargent et al. ACS Energy Lett. 2020, 5, 2796-2801). Summary of the Invention
[0004] This invention provides an interface-modified electron transport layer, in which GCC material is used to modify the SnO2 electron transport layer to regulate the work function of SnO2 and compensate for its intrinsic defects. The modified SnO2 electron transport layer is then used in perovskite solar cells (PSCs) to improve the photoelectric conversion efficiency and stability of the corresponding devices.
[0005] One objective of this invention is to provide an interface-modified electron transport layer, comprising a SnO2 thin film and an ADA-type large π-conjugated material coated on the surface of the SnO2 thin film. This invention utilizes a large π-conjugated compound to modify SnO2 and applies it to a PSC (Power Segment Cell).
[0006] In the aforementioned interface-modified electron transport layer, the thickness of the SnO2 thin film is 5–60 nm, preferably 5–30 nm; the thickness of the ADA-type large π conjugated material is 1–15 nm, preferably 1–10 nm.
[0007] Specifically, the structural formula of the ADA-type large π conjugated material (GCC) is as follows:
[0008]
[0009] The donor unit of the GCC compound is an indara-dithiophene[3,2-b]thiophene derivative. The R1 group connected to the indara-dithiophene[3,2-b]thiophene derivative is an alkyl chain, and R2 is a conjugated group with a strong electron-withdrawing effect. As a preferred embodiment of the present invention, in the above structural formula, R1 is an alkyl group with 1 to 15 carbon atoms, preferably an alkyl group with 3 to 10 carbon atoms; R2 is a conjugated group, preferably a conjugated group containing a benzene ring or thiophene.
[0010] The second objective of this invention is to provide a method for preparing the above-mentioned interface-modified electron transport layer, which includes coating a solution containing the ADA-type large π conjugated material onto the surface of SnO2 to obtain the interface-modified electron transport layer.
[0011] Specifically, the ADA-type large π conjugated material solution is obtained by stirring the ADA-type large π conjugated material and solvent evenly under heating conditions. Preferably, the solvent in the ADA-type large π conjugated material solution is selected from organic solvents, which can be labeled as organic solvent S1, and is preferably selected from at least one of chloroform, chlorobenzene, o-dichlorobenzene, and toluene; the concentration of the ADA-type large π conjugated material solution is 0.1-10 mg / mL, preferably 0.1-5 mg / mL; the heating temperature is 40-100℃, preferably 40-70℃.
[0012] The third objective of this invention is to provide a perovskite solar cell, comprising a cathode substrate, the interface-modified electron transport layer described above or obtained by the above preparation method, a photoactive layer, a hole transport layer, and an anode material.
[0013] Specifically, the cathode substrate is ITO glass;
[0014] The photoactive layer is a perovskite photoactive layer, which can be selected from various perovskite photoactive layers already existing in existing perovskite solar cells, and is preferably a mixed dual-cation perovskite (FAPbI3). 1-x (MAPbBr3) x , where x is 0.03 to 0.2;
[0015] The thickness of the photoactive layer is 200–700 nm, preferably 300–500 nm;
[0016] The hole transport layer is 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) and molybdenum trioxide (MoO3). Preferably, the thickness of the 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is 100-250 nm, and the thickness of the molybdenum trioxide is 5-20 nm. More preferably, the thickness of the 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is 120-200 nm, and the thickness of the molybdenum trioxide is 3-12 nm.
[0017] The anode material is a metallic material, preferably at least one of silver and aluminum;
[0018] The thickness of the anode material is 50–200 nm, preferably 50–120 nm.
[0019] In one specific embodiment of the present invention, the device structure of the PSC based on the interface-modified electron transport layer is ITO / SnO2 / GCC / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag, e.g. Figure 2 As shown.
[0020] The fourth objective of this invention is to provide a method for fabricating the aforementioned perovskite solar cell, comprising: cleaning the cathode substrate surface, spin-coating an electron transport layer, modifying the interface of the electron transport layer, spin-coating a photoactive layer, spin-coating a hole transport layer, and evaporating an anode material. Except for the step of modifying the interface of the electron transport layer, the other steps can be adopted from existing techniques for fabricating perovskite solar cells.
[0021] In a preferred embodiment of the method for preparing perovskite solar cells of the present invention, the method specifically includes the following steps:
[0022] Step (1) After cleaning the ITO substrate with a solvent, it is dried;
[0023] Step (2) Disperse the SnO2 nanoparticle colloidal solution in water, then spin-coat it onto the ITO substrate treated in step (1), and anneal it to obtain the SnO2 electron transport layer;
[0024] Step (3) spin-coating the ADA-type large π conjugated material solution onto the SnO2 electron transport layer to obtain the modified SnO2 electron transport layer;
[0025] In step (4), lead iodide is dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide to obtain precursor solution 1; amine halide is dissolved in an organic solvent to obtain precursor solution 2; precursor solution 1 and precursor solution 2 are spin-coated onto the surface of the SnO2 electron transport layer modified in step (3) in sequence, and annealed to obtain a material coated with a perovskite photoactive layer.
[0026] In step (5), 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is dissolved in an organic solvent, and tetratert-butylpyridine and lithium bis(trifluoromethanesulfonyl)imide are added to obtain solution 3. Solution 3 is spin-coated onto the perovskite photoactive layer in step (4), and then molybdenum trioxide is evaporated to obtain a material covered with a hole transport layer.
[0027] Step (6) involves vacuum evaporating the anode material onto the surface of the hole transport layer to obtain the perovskite solar cell.
[0028] Specifically, in the above preparation method:
[0029] In step (1), the ITO substrate is cleaned with a solvent. Commonly used solvents and steps for cleaning ITO substrates in the prior art can be employed. A preferred cleaning step is as follows: the ITO substrate is repeatedly rubbed in acetone, and then ultrasonically cleaned in sequence with detergent, deionized water, acetone, anhydrous ethanol, and isopropanol. The ITO substrate dried in step (1) also needs to be treated with ultraviolet ozone.
[0030] In one specific embodiment of the present invention, the ITO surface treatment steps are as follows: the surface of the ITO transparent substrate is repeatedly rubbed with cotton in acetone, then ultrasonically cleaned twice in sequence with detergent, deionized water, acetone, anhydrous ethanol and isopropanol, each time for no less than 20 minutes, and then dried in a vacuum drying oven at 80°C for 15 minutes; finally, it is treated with ultraviolet ozone (UVO) for 15-20 minutes, and the treated ITO substrate is placed in a glove box.
[0031] In a specific embodiment of the present invention, the preparation of the SnO2 thin film in step (2) and the modification of SnO2 with GCC in step (3) are as follows: SnO2 nanoparticle colloidal solution and ultrapure water are mixed in a certain volume ratio and ultrasonically dispersed, and then spin-coated onto a surface-treated cathode substrate ITO, followed by annealing; a certain concentration of GCC solution is heated and stirred evenly, and then spin-coated onto SnO2 to obtain a GCC-modified SnO2 electron transport layer;
[0032] The SnO2 nanoparticle colloidal solution has a mass percentage concentration of 1-20%, preferably 1-10%; and in terms of volume percentage, the SnO2 nanoparticle colloidal solution in step (2) accounts for 10-60% of the total volume of the SnO2 nanoparticle colloidal solution and ultrapure water, preferably 10-30%.
[0033] In step (2), the annealing temperature is 80-300℃ and the annealing time is 30-180min. Preferably, in step (2), the annealing temperature is 140-180℃ and the annealing time is 30-60min.
[0034] The concentration of the ADA-type large π conjugated material (GCC) solution is 0.1–10 mg / mL, preferably 0.1–5 mg / mL.
[0035] In a specific embodiment of the present invention, the preparation steps of the perovskite optical active layer in step (4) are as follows: lead iodide (PbI2) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to obtain precursor solution 1; amine halide is dissolved in an organic solvent in a certain mass ratio, wherein the organic solvent can be labeled as organic solvent S2, and can be selected from commonly used isopropanol (IPA) solvent to obtain precursor solution 2; solutions 1 and 2 are spin-coated onto the surface of the electron transport layer in a two-step method, and annealed to obtain the perovskite optical active layer;
[0036] Wherein, by volume percentage, the dimethyl sulfoxide (DMSO) accounts for 1 to 40% of the total volume of the N,N-dimethylformamide and dimethyl sulfoxide mixed solvent, preferably 3 to 20%;
[0037] The haloamine is selected from formamidine, methyl bromide, and chloromethylamine. Preferably, based on the total mass of formamidine, methyl bromide, and chloromethylamine as 100%, the methyl bromide is 1-60%, preferably 5-30%; the chloromethylamine is 1-60%, preferably 5-30%; and the balance is formamidine.
[0038] The concentration of precursor solution 1 is 400-700 mg / mL, preferably 460-650 mg / mL; the concentration of precursor solution 2 is 0.01-0.2 mg / mL, preferably 0.05-0.15 mg / mL.
[0039] The annealing temperature is 70–200°C, preferably 100–150°C.
[0040] In a specific embodiment of the present invention, the spin-coating preparation of the hole transport layer in step (5) is as follows: a certain mass of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) is dissolved in an organic solvent, which can be labeled as organic solvent S3, and can be selected from commonly used chlorobenzene solvent, and a certain volume of tBP (tetra-tert-butylpyridine) and lithium bis(trifluoromethanesulfonylimide) (LiTFSI) is added. The resulting solution is spin-coated on the perovskite photoactive layer, and then the hole transport layer MoO3 is evaporated on the surface of the above-mentioned Spiro-OMeTAD to obtain the hole transport layer;
[0041] Specifically, based on a dosage of 100 mg of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, the dosage of the organic solvent is 1-2 mL, the dosage of the tetratert-butylpyridine is 20-60 μL, and the dosage of lithium bis(trifluoromethanesulfonyl)imide is 1-30 mg; preferably, based on a dosage of 100 mg of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene, the dosage of the organic solvent is 1-1.5 mL, the dosage of the tetratert-butylpyridine is 30-50 μL, and the dosage of lithium bis(trifluoromethanesulfonyl)imide is 5-15 mg.
[0042] The vapor deposition conditions are that the vapor deposition chamber pressure is maintained at 2 × 10⁻⁶. -4 Below Pa, Molybdenum trioxide was deposited at a certain rate.
[0043] In a specific embodiment of the present invention, the anode preparation in step (6) above is as follows: the thin film is prepared by vacuum evaporation, preferably, the vacuum evaporation conditions are that the pressure in the evaporation chamber is maintained at 1×10⁻⁶. -4 Below Pa, The rate at which silver or aluminum is deposited is evaporated.
[0044] This invention proposes an electron transport layer SnO2 modified with an ADA-type large π conjugated material (GCC), thereby achieving work function modulation and defect compensation of SnO2. Experiments show that the introduction of this material can form a dipole in SnO2, effectively reducing the work function of SnO2. In addition, GCC effectively passivates defects, and the electron mobility of SnO2 is also significantly improved; when applied to PSC, the photoelectric conversion efficiency and stability of the corresponding device are also significantly improved.
[0045] This invention proposes using GCC to modify SnO2 and applying it as an electron transport material in PSC, thereby improving the battery's efficiency and stability. Compared with existing technologies, the advantages and beneficial effects of this invention mainly include:
[0046] (1) In the interface-modified electron transport layer provided by the present invention, GCC forms a dipole on the SnO2 surface, which reduces the work function of SnO2 and better matches the energy level of perovskite.
[0047] (2) The oxygen vacancy defects of SnO2 are passivated, which effectively suppresses the interfacial recombination of charges.
[0048] (3) When the interface-modified electron transport layer provided by the present invention is applied to PSC, the crystallinity of perovskite is significantly improved, and the photoelectric conversion efficiency of the device is increased from 20% to more than 22%. Attached Figure Description
[0049] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell provided by the present invention.
[0050] Figure 2 The JV curve of GCC / SnO2 obtained in Embodiment 1 of the present invention is shown, where the horizontal axis represents voltage V (V) and the vertical axis represents current density J (mA·cm). -2 Curve 1 represents the unmodified perovskite solar cell device of Example 1, and curve 2 represents the perovskite solar cell device of Example 1 modified with GCC1. Detailed Implementation
[0051] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0052] The testing instruments and conditions used in this embodiment are as follows:
[0053] The JV curve is measured under specific illumination and temperature conditions. According to internationally recognized standard testing conditions for ground-mounted photovoltaic modules, the atmospheric quality is AM1.5, and the standard cell's solar irradiance is 1000 W·m². -2 The test temperature was 25℃. Irradiation was provided using a Japanese XES-70S1 solar simulator, and the current and voltage outputs were recorded using a Keithley 2400 from Keithley Instruments to obtain the JV curve of the battery. During the test, a photomask was used to fix the active layer with an illumination area of 0.1 cm². 2 .
[0054] Thickness measurement: Spectroscopic ellipsometer (M-2000V, JAWoollam Co., Lincoln, NE, USA).
[0055] The raw materials used in the examples are from the following sources:
[0056] The ITO used in the experiment had a thickness of 1.2 mm, a transmittance of >80%, and a sheet resistance of 10 Ω / sq, and was purchased from Shenzhen Nanbo Co., Ltd. The ADA-type large π conjugate material was purchased from Organtec Ltd.
[0057] acetone Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Anhydrous ethanol Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Isopropanol Analytical Pure Sinopharm Chemical Reagent Co., Ltd. DMF 99.8%, super dry Beijing Innocare Technology Co., Ltd. DMSO 99.8%, super dry Beijing Innocare Technology Co., Ltd. chlorobenzene 99.9%, super dry Sigma Aldrich Chloroform 99.9%, super dry Sigma Aldrich Toluene 99.9%, super dry Sigma Aldrich Lead iodide 99.99% Xi'an Baolait Co., Ltd. Iodine Methylamidine 99.99% Xi'an Baolait Co., Ltd. Chloromethylamine 99.99% Xi'an Baolait Co., Ltd. methyl bromide 99.99% Xi'an Baolait Co., Ltd. Spiro-OMeTAD 99.5% Xi'an Baolait Co., Ltd. Acetonitrile 99.9% Sigma Aldrich LiTFSI 99.0% Xi'an Baolai Optoelectronics Co., Ltd. Silver (Ag) 99.999% Zhongnuo New Materials Technology Co., Ltd.
[0058] Example 1
[0059] Fabrication of perovskite solar cells:
[0060] In this embodiment, a perovskite solar cell device structure using an interface modification layer formed by solution drop coating of the ADA-type large π conjugated material GCC1 (the specific molecular formulas of the R1 and R2 groups are shown in Formula 2 below) is as follows: ITO / SnO2 / GCC1 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0061]
[0062] Formula 2, the chemical structural formula of GCC1 involved in this invention
[0063] (1) The steps for ITO surface treatment are as follows: The surface of the ITO transparent substrate is repeatedly rubbed with cotton in acetone until no trace of impurities is left. Then, it is ultrasonically cleaned twice in sequence with detergent, deionized water, acetone, anhydrous ethanol, and isopropanol, each time for no less than 20 minutes. Before use, the ITO needs to be dried with nitrogen and placed in an 80℃ vacuum drying oven for 15 minutes; then treated with ultraviolet ozone (UVO) for 15 minutes, and the treated ITO substrate is placed in a glove box.
[0064] (2) The preparation of SnO2 thin film and the steps of modifying SnO2 with GCC1 are as follows: 3% SnO2 nanoparticle colloidal solution and ultrapure water were mixed at a volume ratio of 1:3 and ultrasonically dispersed. Then, it was spin-coated onto the cathode substrate ITO that had undergone surface treatment in step (1) at a speed of 5000 rpm for 30 s; subsequently, it was annealed at 180℃ for 45 min to obtain SnO2 thin film. The GCC1 solution was stirred evenly and spin-coated onto SnO2 to obtain a GCC1-modified SnO2 electron transport layer, wherein the thickness of GCC1 was 5 nm and the thickness of SnO2 was 15 nm; the GCC1 solution was prepared by the following steps: 1 mg of GCC1 sample was weighed and dissolved in 1 mL of toluene solvent, and heated and stirred at 40℃ for 6 h.
[0065] (3) The preparation steps of the perovskite optically active layer are as follows: A two-step method is used to spin-coat the perovskite precursor solution onto the surface of the above-mentioned electron transport layer, specifically as follows: Lead iodide (PbI2) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (DMF:DMSO = 97:3) to obtain precursor solution 1 with a concentration of 1.3 mM; formamidine iodocarbamate (FAI), methyl bromide (MABr), and methyl chloromethylamine (MACl) are dissolved in isopropanol (IPA) solvent in a certain mass ratio (FAI:MABr:MACl = 60:6:6) to obtain precursor solution 2 (wherein, the concentration of FAI is 0.06 mg / ml; the concentration of MABr is 0.006 mg / ml; and the concentration of MACl is 0.006 mg / ml). Precursor solution 1 and precursor solution 2 are filtered separately using a polytetrafluoroethylene filter. A two-step method was used, in which filtered solutions 1 and 2 were spin-coated onto the surface of the electron transport layer at a speed of 4000 rpm, and then annealed at 100°C for 60 min to obtain a perovskite optical active layer with a thickness of 360 nm.
[0066] (4) A hole transport layer Spiro-OMeTAD and MoO3 were prepared on the perovskite layer. The preparation process of Spiro-OMeTAD was as follows: 73 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene, and 23 μL of tBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI / acetonitrile solution (concentration of 520 mg / mL) were added. The solution was spin-coated onto the perovskite layer at a speed of 3500 rpm to obtain a Spiro-OMeTAD film with a thickness of 160 nm. A hole transport layer MoO3 was deposited on the surface of the above Spiro-OMeTAD under a vacuum degree lower than 2 × 10⁻⁶. -4 Pa, the rate is approximately The thickness is 10nm.
[0067] (5) An anode layer Ag is deposited on the surface of the hole transport layer; under a vacuum of 1×10⁻⁶. -4 Below Pa, Ag was deposited at a rate of 90 nm to obtain a perovskite solar cell device with a GCC1 modified SnO2 electron transport layer, consisting of ITO / SnO2 / GCC1 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag.
[0068] Comparative Example 1
[0069] Fabrication of perovskite solar cells:
[0070] The preparation method in Example 1 is the same, except that step (2) only prepares SnO2 film and does not include the step of modifying SnO2 with GCC1 to obtain unmodified perovskite solar cell device.
[0071] Appendix Figure 2 This is a graph showing the current density versus voltage relationship between the unmodified perovskite solar cell device in Comparative Example 1 and the GCC1-modified perovskite solar cell device in Example 1. Curve 1 represents the open-circuit voltage (V) of the unmodified perovskite solar cell device in Comparative Example 1. oc The voltage is 1.10V, and the short-circuit current (J) is... sc The value is 23.89 mA / cm. 2 The fill factor (FF) is 78.04%; while the perovskite solar cell modified with GCC1 in Example 1 (curve 2) has a Vfill factor. oc 1.13V, J sc 24.77 mA / cm 2 The field-effect ratio (FF) was 80.10%, and the photoelectric conversion efficiency (PCE) increased from 20.50% to 22.45%. This indicates that the SnO2 electron transport layer modified with GCC1 can effectively reduce surface defects, effectively suppress charge interface recombination, enhance carrier separation efficiency and transport efficiency, and ultimately improve the optoelectronic performance of the device.
[0072] Example 2
[0073] Fabrication of perovskite solar cells:
[0074] In this embodiment, a perovskite solar cell device structure using an interface modification layer formed by solution drop coating of the ADA-type large π conjugated material GCC2 (the specific molecular formulas of the R1 and R2 groups are shown in Formula 3 below) is as follows: ITO / SnO2 / GCC2 / (FAPbI3). 1-x (MAPbBr3)x / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0075]
[0076] Formula 3, the specific chemical structural formula of GCC2 involved in this invention.
[0077] (1) The steps for ITO surface treatment are as follows: The surface of the ITO transparent substrate is repeatedly rubbed with cotton in acetone until no trace of impurities is left. Then, it is ultrasonically cleaned twice in sequence with detergent, deionized water, acetone, anhydrous ethanol, and isopropanol, each time for no less than 20 minutes. Before use, the ITO needs to be dried with nitrogen and placed in an 80℃ vacuum drying oven for 15 minutes; then treated with ultraviolet ozone (UVO) for 20 minutes, and the treated ITO substrate is placed in a glove box.
[0078] (2) The preparation of SnO2 thin film and the steps of modifying SnO2 with GCC2 are as follows: 5% SnO2 nanoparticle colloidal solution and ultrapure water are mixed at a volume ratio of 1:5 and ultrasonically dispersed. Then, it is spin-coated onto the cathode substrate ITO that has undergone surface treatment in step (1) at a speed of 4000 rpm for 30 s; subsequently, it is annealed at 160℃ for 35 min to obtain SnO2 thin film. The GCC2 solution is heated and stirred evenly, and then spin-coated onto SnO2 to obtain a GCC2-modified SnO2 electron transport layer, wherein the thickness of GCC2 is 5 nm and the thickness of SnO2 is 13 nm; the specific molecular formulas of R1 and R2 groups in GCC2 are shown in Formula 3; the GCC2 solution is prepared by the following steps: 2 mg of GCC2 sample is weighed and dissolved in 1 mL of chloroform solvent, and heated and stirred at 40℃ for 6 h.
[0079] (3) The preparation steps of the perovskite optically active layer are as follows: A two-step method is used to spin-coat the perovskite precursor solution onto the surface of the above-mentioned electron transport layer, specifically as follows: Lead iodide (PbI2) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (DMF:DMSO = 95:5) to obtain precursor solution 1 with a concentration of 1.5 mM; formamidine iodocarbamate (FAI), methyl bromide (MABr), and methyl chloromethylamine (MACl) are dissolved in isopropanol (IPA) solvent in a certain mass ratio (FAI:MABr:MACl = 90:9:9) to obtain precursor solution 2 (wherein, the concentration of FAI is 0.09 mg / ml; the concentration of MABr is 0.009 mg / ml; and the concentration of MACl is 0.009 mg / ml). Precursor solution 1 and precursor solution 2 are filtered separately using a polytetrafluoroethylene filter. A two-step method was used, in which filtered solutions 1 and 2 were spin-coated onto the surface of the electron transport layer at a speed of 5000 rpm, and then annealed at 150°C for 30 min to obtain a perovskite optical active layer with a thickness of 380 nm.
[0080] (4) A hole transport layer Spiro-OMeTAD and MoO3 were prepared on the perovskite layer. The preparation process of Spiro-OMeTAD was as follows: 80 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene, and 25 μL of tBP (tetra-tert-butylpyridine) and 20 μL of LiTFSI / acetonitrile solution (concentration of 520 mg / mL) were added. The solution was spin-coated onto the perovskite layer at a speed of 4500 rpm to obtain a 185 nm Spiro-OMeTAD film. A hole transport layer MoO3 was then deposited on the surface of the Spiro-OMeTAD under a vacuum degree lower than 2 × 10⁻⁶. -4 Pa, the rate is approximately The thickness is 8nm.
[0081] (5) An anode layer Ag is deposited on the surface of the hole transport layer; under a vacuum of 1×10⁻⁶. -4 Below Pa, Ag was deposited at a rate of 100 nm to obtain a perovskite solar cell device with a GCC2 modified SnO2 electron transport layer: ITO / SnO2 / GCC2 / (FAPbI3). 0.85 (MAPbBr3) 0.15 / Spiro-OMeTAD / MoO3 / Ag.
[0082] The SnO2 electron transport layer modified with GCC2 can effectively reduce surface defects, effectively suppress charge recombination at the interface, enhance carrier separation efficiency and transport efficiency, and ultimately improve the optoelectronic performance of the device.
[0083] Example 3
[0084] Fabrication of perovskite solar cells:
[0085] In this embodiment, a perovskite solar cell device structure using an interface modification layer formed by solution drop coating of the ADA-type large π conjugated material GCC3 (the specific molecular formulas of the R1 and R2 groups are shown in Formula 4 below) is as follows: ITO / SnO2 / GCC3 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0086]
[0087] Formula 4, the specific chemical structural formula of GCC3 involved in this invention.
[0088] (1) The steps for ITO surface treatment are as follows: The surface of the ITO transparent substrate is repeatedly rubbed with cotton in acetone until no trace of impurities is left. Then, it is ultrasonically cleaned twice in sequence with detergent, deionized water, acetone, anhydrous ethanol, and isopropanol, each time for no less than 20 minutes. Before use, the ITO needs to be dried with nitrogen and placed in an 80℃ vacuum drying oven for 15 minutes; then treated with ultraviolet ozone (UVO) for 15-20 minutes, and the treated ITO substrate is placed in a glove box.
[0089] (2) The preparation of SnO2 thin film and the steps of modifying SnO2 with GCC3 are as follows: SnO2 nanoparticle colloidal solution with a mass percentage concentration of 10% and ultrapure water are mixed at a volume ratio of 1:7 and ultrasonically dispersed. Then, it is spin-coated onto the cathode substrate ITO that has undergone surface treatment in step (1) at a speed of 3000 rpm for 30 s; then, it is annealed at 140℃ for 30 min to obtain SnO2 thin film. GCC3 solution is heated and stirred evenly, and then spin-coated onto SnO2 to obtain GCC3 modified SnO2 electron transport layer, wherein the thickness of GCC3 is 7 nm and the thickness of SnO2 is 18 nm; the specific molecular formulas of R1 and R2 groups in GCC3 are as shown in Formula 4; GCC3 solution is prepared by the following steps: 1 mg of GCC3 sample is weighed and dissolved in 1 mL of chlorobenzene solvent, and heated and stirred at 60℃ for 10 h.
[0090] (3) The preparation steps of the perovskite optically active layer are as follows: A two-step method is used to spin-coat the perovskite precursor solution onto the surface of the above-mentioned electron transport layer, specifically as follows: Lead iodide (PbI2) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (DMF:DMSO = 96:4) to obtain precursor solution 1 with a concentration of 1.6 mM; formamidine iodocarbamate (FAI), methyl bromide (MABr), and methyl chloromethylamine (MACl) are dissolved in isopropanol (IPA) solvent in a certain mass ratio (FAI:MABr:MACl = 90:9:9) to obtain precursor solution 2 (wherein, the concentration of FAI is 0.09 mg / ml; the concentration of MABr is 0.009 mg / ml; and the concentration of MACl is 0.009 mg / ml). Precursor solution 1 and precursor solution 2 are filtered separately using a polytetrafluoroethylene filter. A two-step method was used, in which filtered solutions 1 and 2 were spin-coated onto the surface of the electron transport layer at a speed of 5000 rpm, and then annealed at 150°C for 35 min to obtain a perovskite optical active layer with a thickness of 370 nm.
[0091] (4) A hole transport layer Spiro-OMeTAD and MoO3 were prepared on the perovskite layer. The preparation process of Spiro-OMeTAD was as follows: 94 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene, and 30 μL of tBP (tetra-tert-butylpyridine) and 23 μL of LiTFSI / acetonitrile solution (concentration 520 mg / mL) were added. The solution was spin-coated onto the perovskite layer at a speed of 5500 rpm to obtain a Spiro-OMeTAD film with a thickness of 190 nm. A hole transport layer MoO3 was deposited on the surface of the above Spiro-OMeTAD under a vacuum degree lower than 2 × 10⁻⁶. -4 Pa, the rate is approximately The thickness is 8nm.
[0092] (5) An anode layer Ag is deposited on the surface of the hole transport layer; under a vacuum of 1×10⁻⁶. -4 Below Pa, Ag was deposited at a rate of 80 nm to obtain a perovskite solar cell device with a SnO2 electron transport layer modified by a GCC3-type large π-conjugated compound: ITO / SnO2 / GCC3 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag.
[0093] The SnO2 electron transport layer modified with GCC3 can effectively reduce surface defects, effectively suppress charge recombination at the interface, enhance carrier separation efficiency and transport efficiency, and ultimately improve the optoelectronic performance of the device.
[0094] Example 4
[0095] Fabrication of perovskite solar cells:
[0096] In this embodiment, a perovskite solar cell device structure using an interface modification layer formed by solution drop coating of the ADA-type large π conjugated material GCC4 (the specific molecular formulas of the R1 and R2 groups are shown in Formula 5 below) is as follows: ITO / SnO2 / GCC4 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag. The specific preparation process is as follows:
[0097]
[0098] Formula 5, the specific chemical structural formula of GCC4 involved in this invention.
[0099] (1) The steps for ITO surface treatment are as follows: The surface of the ITO transparent substrate is repeatedly rubbed with cotton in acetone until no trace of impurities is left. Then, it is ultrasonically cleaned twice in sequence with detergent, deionized water, acetone, anhydrous ethanol, and isopropanol, each time for no less than 20 minutes. Before use, the ITO needs to be dried with nitrogen and placed in an 80℃ vacuum drying oven for 15 minutes; then treated with ultraviolet ozone (UVO) for 15-20 minutes, and the treated ITO substrate is placed in a glove box.
[0100] (2) The preparation of SnO2 thin film and the steps of modifying SnO2 with GCC4 are as follows: 3% SnO2 nanoparticle colloidal solution and ultrapure water are mixed at a volume ratio of 1:5 and ultrasonically dispersed for 30 min. Then, it is spin-coated onto the cathode substrate ITO that has undergone surface treatment in step (1) at a speed of 4000 rpm for 30 s; subsequently, it is annealed at 150℃ for 35 min to obtain SnO2 thin film. The GCC4 solution is heated and stirred evenly, and then spin-coated onto SnO2 to obtain a GCC4-modified SnO2 electron transport layer, wherein the thickness of GCC4 is 8 nm and the thickness of SnO2 is 12 nm; the specific molecular formulas of R1 and R2 groups in GCC4 are as shown in Formula 5; the GCC4 solution is prepared by the following steps: 4 mg of GCC4 sample is weighed and dissolved in 1 mL of chlorobenzene solvent, and heated and stirred at 60℃ for 10 h.
[0101] (3) The preparation steps of the perovskite optically active layer are as follows: A two-step method is used to spin-coat the perovskite precursor solution onto the surface of the above-mentioned electron transport layer, specifically as follows: Lead iodide (PbI2) is dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (DMF:DMSO = 95:5) to obtain precursor solution 1 with a concentration of 1.4 mM; formamidine iodocarbamate (FAI), methyl bromide (MABr), and methyl chloromethylamine (MACl) are dissolved in isopropanol (IPA) solvent in a certain mass ratio (FAI:MABr:MACl = 72:7.2:7.2) to obtain precursor solution 2 (wherein, the concentration of FAI is 0.072 mg / ml; the concentration of MABr is 0.0072 mg / ml; and the concentration of MACl is 0.0072 mg / ml). Precursor solution 1 and precursor solution 2 are filtered separately using a polytetrafluoroethylene filter. A two-step method was used, in which filtered solutions 1 and 2 were spin-coated onto the surface of the electron transport layer at a speed of 4500 rpm, and then annealed at 150°C for 30 min to obtain a perovskite optical active layer with a thickness of 350 nm.
[0102] (4) A hole transport layer Spiro-OMeTAD and MoO3 were prepared on the perovskite layer. The preparation process of Spiro-OMeTAD was as follows: 73 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene, and 23 μL of tBP (tetra-tert-butylpyridine) and 18 μL of LiTFSI / acetonitrile solution (concentration of 520 mg / mL) were added. The solution was spin-coated onto the perovskite layer at a speed of 3500 rpm to obtain a Spiro-OMeTAD film with a thickness of 160 nm. A hole transport layer MoO3 was deposited on the surface of the above Spiro-OMeTAD under a vacuum degree lower than 2 × 10⁻⁶. -4 Pa, the rate is approximately The thickness is 8nm.
[0103] (5) An anode layer Ag is deposited on the surface of the hole transport layer; under a vacuum of 1×10⁻⁶. -4 Below Pa, Ag was deposited at a rate of 90 nm to obtain a perovskite solar cell device with a GCC4-modified SnO2 electron transport layer: ITO / SnO2 / GCC4 / (FAPbI3). 1-x (MAPbBr3) x / Spiro-OMeTAD / MoO3 / Ag.
[0104] The above embodiments illustrate in detail the materials and fabrication process of perovskite solar cells with GCC-modified SnO2 electron transport layers.
[0105] The above detailed description further illustrates the purpose, technical solution, and beneficial effects of the invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A perovskite solar cell, comprising a cathode substrate, an interface-modified electron transport layer, a photoactive layer, a hole transport layer, and an anode material, wherein the interface-modified electron transport layer comprises a SnO2 thin film and an ADA-type large π conjugated material coated on the surface of the SnO2 thin film, the ADA-type large π conjugated material having the following structural formula: ; in, R1 is an alkyl group having 1 to 15 carbon atoms; R2 is... , or .
2. The perovskite solar cell according to claim 1, characterized in that, The thickness of the SnO2 film is 5~60 nm; and / or, The thickness of the ADA-type large π conjugated material is 1~15nm.
3. The perovskite solar cell according to claim 2, characterized in that, The thickness of the SnO2 film is 5~30 nm; and / or, The thickness of the ADA-type large π conjugated material is 1~10 nm.
4. The perovskite solar cell according to claim 1, characterized in that, R1 is an alkyl group having 3 to 10 carbon atoms.
5. The perovskite solar cell according to claim 1, characterized in that, The method for preparing the interface-modified electron transport layer includes coating a solution containing the ADA-type large π conjugated material onto the surface of SnO2 to obtain the interface-modified electron transport layer.
6. The perovskite solar cell according to claim 5, characterized in that, The ADA-type large π conjugated material solution is obtained by stirring the ADA-type large π conjugated material and solvent under heating conditions until homogeneous.
7. The perovskite solar cell according to claim 6, characterized in that, The solvent in the ADA-type large π conjugated material solution is selected from organic solvents; and / or... The concentration of the ADA-type large π conjugated material solution is 0.1~10 mg / mL; and / or, The heating temperature is 40~100℃.
8. The perovskite solar cell according to claim 7, characterized in that, The solvent in the ADA-type large π-conjugated material solution is selected from at least one of chloroform, chlorobenzene, o-dichlorobenzene, and toluene; and / or, The concentration of the ADA-type large π conjugated material solution is 0.1~5 mg / mL; and / or, The heating temperature is 40~70℃.
9. The perovskite solar cell according to claim 1, characterized in that, The cathode substrate is ITO glass; and / or, The photoactive layer is a perovskite photoactive layer; and / or, The thickness of the photoactive layer is 200~700 nm; and / or, The hole transport layer comprises a 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene layer and a molybdenum trioxide layer; and / or, The anode material is a metallic material; and / or, The thickness of the anode material is 50~200 nm.
10. The perovskite solar cell according to claim 9, characterized in that, The photoactive layer is a mixed bis-cationic perovskite; and / or, The thickness of the photoactive layer is 300~500 nm; and / or, The thickness of the 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene layer is 100~250 nm, and the thickness of the molybdenum trioxide layer is 5~20 nm; and / or, The anode material is at least one of silver and aluminum; and / or, The thickness of the anode material is 50~120 nm.
11. The perovskite solar cell according to claim 10, characterized in that, The thickness of the 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene layer is 120~200 nm, and the thickness of the molybdenum trioxide layer is 3~12 nm.
12. A method for preparing a perovskite solar cell according to any one of claims 1 to 11, comprising: The process involves cleaning the cathode substrate surface, spin-coating an electron transport layer, modifying the interface of the electron transport layer, spin-coating a photoactive layer, spin-coating a hole transport layer, and evaporating the anode material.
13. The preparation method according to claim 12, characterized in that, The preparation method specifically includes the following steps: Step (1) After cleaning the ITO substrate with a solvent, it is dried; Step (2) Disperse the SnO2 nanoparticle colloidal solution in water, then spin-coat it onto the ITO substrate treated in step (1), and anneal it to obtain the SnO2 electron transport layer; Step (3) Spin-coat the ADA-type large π conjugated material solution onto the SnO2 electron transport layer to obtain the modified SnO2 electron transport layer; In step (4), lead iodide is dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide to obtain precursor solution 1; amine halide is dissolved in an organic solvent to obtain precursor solution 2; precursor solution 1 and precursor solution 2 are spin-coated onto the surface of the SnO2 electron transport layer modified in step (3) in sequence, and annealed to obtain a material coated with a perovskite photoactive layer. In step (5), 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene is dissolved in an organic solvent, and tetratert-butylpyridine and lithium bis(trifluoromethanesulfonyl)imide are added to obtain solution 3. Solution 3 is spin-coated onto the perovskite photoactive layer in step (4), and then molybdenum trioxide is evaporated to obtain a material covered with a hole transport layer. Step (6) involves vacuum evaporating the anode material onto the surface of the hole transport layer to obtain the perovskite solar cell.
14. The preparation method according to claim 13, characterized in that, In step (2), the mass percentage concentration of the SnO2 nanoparticle colloidal solution is 1-20%; and / or, In terms of volume percentage, the SnO2 nanoparticle colloidal solution in step (2) accounts for 10-60% of the total volume of the SnO2 nanoparticle colloidal solution and water; and / or, In step (3), the concentration of the ADA-type large π conjugated material solution is 0.1~10 mg / mL; and / or, In terms of volume percentage, dimethyl sulfoxide accounts for 1-40% of the total volume of the N,N-dimethylformamide and dimethyl sulfoxide mixed solvent in step (4); and / or, The halogenated amine in step (4) is selected from iodoformamidine, methyl bromide, and chloromethylamine; and / or, In step (4), the concentration of precursor solution 1 is 400~700 mg / mL; and / or, In step (4), the concentration of precursor solution 2 is 0.01~0.2 mg / mL; and / or, In step (5), based on the amount of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene being 100 mg, the amount of the organic solvent being 1-2 mL, the amount of tetratert-butylpyridine being 20-60 µL, and the amount of lithium bis(trifluoromethanesulfonyl)imide being 1-30 mg.
15. The preparation method according to claim 14, characterized in that, In step (2), the mass percentage concentration of the SnO2 nanoparticle colloidal solution is 1-10%; and / or, In terms of volume percentage, the SnO2 nanoparticle colloidal solution in step (2) accounts for 10-30% of the total volume of the SnO2 nanoparticle colloidal solution and water; and / or, In step (3), the concentration of the ADA-type large π conjugated material solution is 0.1~5 mg / mL; and / or, In step (4), dimethyl sulfoxide accounts for 3-20% of the total volume of the N,N-dimethylformamide and dimethyl sulfoxide mixed solvent; and / or, Based on the total mass of the aforementioned formamidine, methylbromomethylamine, and chloromethylamine being 100%, the methylbromomethylamine comprises 1-60%, and the chloromethylamine comprises 1-60%; and / or, In step (4), the concentration of precursor solution 1 is 460~650 mg / mL; and / or, In step (4), the concentration of precursor solution 2 is 0.05~0.15 mg / mL; and / or, Based on the dosage of 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene being 100 mg, the dosage of the organic solvent is 1-1.5 mL, the dosage of the tetratert-butylpyridine is 30-50 µL, and the dosage of lithium bis(trifluoromethanesulfonyl)imide is 5-15 mg.
16. The preparation method according to claim 15, characterized in that, Based on the total mass of the iodoformin, methyl bromide, and methyl chloromethylamine being 100%, the methyl bromide comprises 5-30% and the methyl chloromethylamine comprises 5-30%.
17. The preparation method according to claim 13, characterized in that, The ITO substrate dried in step (1) also needs to undergo ultraviolet ozone treatment; and / or, In step (2), the annealing temperature is 80~300 ℃, and the annealing time is 30~180 min; and / or, The annealing temperature in step (4) is 70~200℃; and / or, The vapor deposition conditions in step (5) are that the vapor deposition chamber pressure is maintained at 2 × 10⁻⁶. -4 Molybdenum trioxide is deposited at a rate of 0.1–1 Å / s below Pa; and / or, In step (6), the vacuum evaporation conditions are that the pressure in the evaporation chamber is maintained at 1×10⁻⁶. -4 Silver or aluminum is deposited at a rate of 0.5~2 Å / s below Pa.
18. The preparation method according to claim 14, characterized in that, In step (2), the annealing temperature is 140~180℃, and the annealing time is 30~60min; and / or, The annealing temperature in step (4) is 100~150 ℃.
